2013
DOI: 10.7314/apjcp.2013.14.3.1791
|View full text |Cite
|
Sign up to set email alerts
|

Growth Inhibition and Apoptosis Induction of Human Umbilical Vein Endothelial Cells by Apogossypolone

Abstract: Aims and Background: Prostate cancer is one of the most common malignant tumors in the male reproductive system, which causes the second most cancer deaths of males, and control of angiogenesis in prostate lesions is of obvious importance. This study assessed the effect of apogossypolone (ApoG2)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Apogossypolone (ApoG2) is a novel derivative of gossypol, which is a polyphenolic substance extracted from cottonseed (7). ApoG2 is an effective inhibitor of cancer cell proliferation and suppresses tumor growth by inducing apoptosis (7).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Apogossypolone (ApoG2) is a novel derivative of gossypol, which is a polyphenolic substance extracted from cottonseed (7). ApoG2 is an effective inhibitor of cancer cell proliferation and suppresses tumor growth by inducing apoptosis (7).…”
Section: Introductionmentioning
confidence: 99%
“…ApoG2 is an effective inhibitor of cancer cell proliferation and suppresses tumor growth by inducing apoptosis (7). Additionally, ApoG2 is less toxic to normal cells than gossypol.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, (±)-gossypol can bind to Bcl-2, Bcl-xL, and Mcl-1, which suggests that (±)-gossypol might be an alternative treatment approach associated with apoptosis (Shen et al 2018). Zhan et al (2013) have demonstrated that apogossypolone, a gossypol derivative, induces apoptosis by inhibiting the growth and angiogenesis of HUVECs. Studies have also shown that (±)-gossypol has anti-proliferative effects on various cancer cell lines, such as MCF-7 human breast cancer cells (Jaroszewski et al 1990); PC3 human prostate cancer cells (Jiang et al 2004); WM164, WM56, and WM9 human melanoma cells; human ovarian cancer cells (Wang and Rao 1984); and SW1116, SW1084, and SW407 colon carcinoma cells (Tuszynski and Cossu 1984).…”
Section: Introductionmentioning
confidence: 99%